Physical activity assessment and vascular function in adults with cystic fibrosis and their non-CF peers. Issue 16 (18th August 2022) - Shelley, James; Boddy, Lynne; Knowles, Zoe; Stewart, Claire; Frost, Freddy; Nazareth, Dilip; Walshaw, Martin; Dawson, Ellen
ABSTRACT: An understanding of physical activity (PA) and related health benefits remains limited in adults with Cystic Fibrosis (CF). Raw acceleration data metrics may improve the quality of assessment and further this understanding. The study aimed to compare PA between people with CF (pwCF) and non-CF peers and examine associations between PA, vascular function and health outcome measures. PA was assessed in 62 participants (31 pwCF) using ActiGraph accelerometers. Vascular function (a marker of cardiovascular disease risk) was assessed using flow-mediated dilatation (FMD) in sub-groups of pwCF (n = 12) and matched controls. Average Euclidean norm minus one (ENMO) (total PA) was significantly lower ( p = 0.005) in pwCF (35.09 ± 10.60 m g ), than their non-CF peers (44.62 ± 13.78 m g ). PwCF had PA profiles (intensity gradient) indicative of more time in lower intensity activity (−2.62 ± 0.20, −2.37 ± 0.23). Vigorous activity was positively associated with lung function ( rs  = 0.359) and Quality of Life ( r = 0.412). There were no significant differences ( p = 0.313) in FMD% between pwCF (5.29 ± 2.76%) and non-CF peers (4.34 ± 1.58%) and no associations with PA. PwCF engaged in less moderate-to-vigorous PA and demonstrated a steeper PA profile than their non-CF peers.